(untitled) (Journal of Oriental Studies, 2016)
This article is describing the women’s appearance by contrasting idioms and literary descriptions to each other which in Kazakh, English, and Chinese languages, to compare their difference and similarities; As well as these different descriptions of women’s beauty that denoted every nation which has their own different aerthetic concepts and ethnoculture.